Answer:
5
Step-by-step explanation:
Answer:
43+(x-7)=90
43+(x-7)-43=90-43
(x-7)=46
x-7+7=47+7
x=54
Step-by-step explanation:
a) 9 toilet rolls cost $ 4.23
1 toilet roll costs $ x
9x = 4.23 * 1
x= 4.23 / 9
x = 0.47
So in first case one toilet roll costs $ 0.47.
b) 4 toilet rolls cost $1.96
1 toilet roll costs $ x
4x = 1.96 * 1
x = 1.96 / 4
x = 0.49
So in second case one toilet roll costs $ 0.49.
0.47 < 0.49
The toilet roll in first case is cheaper than the toilet roll in second case.
Hope this heps!
Answer:
First break up 72 into
36 x 2 x -1
Then take the square root of 36
6 square root 2 x -1
Finally make square root -1 = i
6i square root 2 is your answer
Step-by-step explanation:
Answer:
(8, 2 )
Step-by-step explanation:
Given the 2 equations
x + 4y = 16 → (1)
- x + 3y = - 2 → (2)
Adding the 2 equations term by term will eliminate the x- term
0 + 7y = 14
7y = 14 ( divide both sides by 7 )
y = 2
Substitute y = 2 into either of the 2 equations and solve for x
Substituting into (1)
x + 4(2) = 16
x + 8 = 16 ( subtract 8 from both sides )
x = 8
solution is (8, 2 )